2013
DOI: 10.1155/2013/276070
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of ICDAS-II Using Low-Powered Magnification with Light-Emitting Diode Headlight and Alternating Current Impedance Spectroscopy Device for Detection of Occlusal Caries on Primary Molars

Abstract: Early detection of occlusal caries in children is challenging for the dentists, because of the morphology of pit and fissures. The aim of this study was to compare in vitro the diagnostic performance of low-powered magnification with light-emitting diode headlight (LPMLED) using ICDAS-II criteria and AC Impedance Spectroscopy (ACIS) device, on occlusal surfaces of primary molars. The occlusal surfaces of 18 extracted primary molars were examined blindly by two examiners. The teeth were sectioned and examined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
0
15
0
2
Order By: Relevance
“…18 Ari et al assessed the performance of ICDAS-II using low powered magnification with light emitting diode headlight and alternating current impedance spectroscopy device for detection of occlusal caries on primary molars and reported that with magnification, the sensitivity and specificity scores for examiners were 0.87-0.90 and 0.70-0.75, respectively, at the D1 diagnostic threshold, which is lesser than the values reported in our study. 20 But studies that were done previously, without using ICDAS scoring reported better performance with magnification. [14][15][16][17] Thus it can be inferred that the scoring criteria and the conditions of dry and illuminated field used in ICDAS criteria are robust enough to detect the physical changes on the tooth surface, just by unaided visual examination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Ari et al assessed the performance of ICDAS-II using low powered magnification with light emitting diode headlight and alternating current impedance spectroscopy device for detection of occlusal caries on primary molars and reported that with magnification, the sensitivity and specificity scores for examiners were 0.87-0.90 and 0.70-0.75, respectively, at the D1 diagnostic threshold, which is lesser than the values reported in our study. 20 But studies that were done previously, without using ICDAS scoring reported better performance with magnification. [14][15][16][17] Thus it can be inferred that the scoring criteria and the conditions of dry and illuminated field used in ICDAS criteria are robust enough to detect the physical changes on the tooth surface, just by unaided visual examination.…”
Section: Discussionmentioning
confidence: 99%
“…18 Yet another study by Ari et al 2013, evaluated low power magnification with LED light for ICDAS coding of occlusal caries in primary molars, reported good to excellent reproductivity. 20 On the contrary, Mitropoulos et al in 2012 compared the impact of lowpowered magnification on the detection of occlusal caries. The occlusal surfaces of 38 extracted teeth were examined with and without magnification by two examiners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the difficulty in radiographic diagnosis of early lesions may be related to the percentage of demineralization, as it has been reported that 30 to 40% of mineral loss is necessary for the radiographic detection of enamel caries. [21][22][23] In lesions classified as mild per the ICCMS TM , 61.29% were radiographically classified as healthy. These results agree with the study by Bertella et al in 2012 on the x-ray pattern En el presente estudio se encontró una baja correlación entre las categorías de caries propuestas por el ICCMS TM , con relación al sistema de registro radiográfico propuesto, al analizar tanto superficies proximales y oclusales, como superficies interproximales exclusivamente; esto se debe quizá a la poca pérdida de mineral de las lesiones iniciales, las cuales no logran ser percibidas radiolúcidamente.…”
Section: Discussionunclassified
“…De nuevo, la dificultad de diagnóstico radiográfico de lesiones tempranas podría estar relacionada con el porcentaje de desmineralización, ya que se reporta que una pérdida mineral del 30-40% es necesaria para la detección radiográfica de caries de esmalte. [21][22][23] En las lesiones clasificadas como moderadas según el ICCMS of mild lesions on permanent molars, evaluating the association between enamel fissure and radiographic features, finding out that 67.4% of these lesions did not show radiographic radiolucity. 12,22 A second analysis was conducted excluding the occlusal surfaces, since coronal x-rays have proven to be more effective in interproximal surfaces.…”
Section: Discussionunclassified